IMPLIKASI DAN MEKANISME EKSEKUSI OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NO.18/PUU-XVII/2019 DALAM HAL DEBITUR WANPRESTASI - Brigita Cindy Meiliana; Arief Suryono (Jurnal Privat Law, 2023)
This article aims to find out the legal implications of the Constitutional Court Decision No.18 / PUU-XVII / 2019 and the mechanism for the execution of fiduciary object guarantees after the Constitutional Court Decision No.18 / PUU-XVII / 2019. This type of research is normative with the nature of applied and prescriptive research. Based on the results of research and discussion, the most important implications  are  the  reduced  executive  power  of  fiduciary  certificates,  the elimination  of  the  parate  execution  mechanism,  and  inefficiency  in  handling fiduciary guarantee disputes. Meanwhile, the mechanism is longer and more complicated.